Immunological response and implications of Ad26.COV2. S (Janssen COVID-19 vaccine) vaccine in diabetic patients: a prospective cohort study in Ethiopia - Edae, Chala Kenenisa; Tufa Bedada, Abdisa; Teklemariam, Maria Degef; Gudisa, Abera Botore; Adamu, Abdurahman; Gebre, Solomon Genet (Frontiers in Immunology, 2025)
IntroductionPatients with Diabetes are at increased risk of severe COVID-19 and death, thus, it is imperative to provide them with vaccination. Ad26.COV2. S vaccine has proven its efficacy. However, the immunological response of the patients with diabetes in Ethiopia has not been well studied.MethodsThis prospective cohort study assessed immune responses after vaccination with a single dose of the Ad26.COV2.S. The subjects were enrolled diabetic patients who were 18 years old and above and attended a diabetes clinic at Adama Hospital Medical College. A sufficient blood sample was collected from each participant, following established standard protocols. We evaluated correlations among selected immunological parameters (IgG, IgM, CRP, IL6, IFN-Y) and employed statistical techniques such as chi-square tests, independent t-tests, and Generalized Estimating Equations (GEE) to analyze differences between given vaccinated and non-vaccinated cohorts. Generalized Estimating Equations (GEE) are a statistical method for modeling longitudinal or clustered data, particularly useful when dealing with non-normal data like binary or count data, by estimating parameters of a generalized linear model while accounting for potential correlations between observations.ResultsIt was found that vaccinated subjects showed significant alterations in the immune response with IgM elevation and a temporary increase of inflammatory biomarkers CRP and IL-6. Younger age and females were associated with lower inflammatory markers, and no significant effects of lifestyle factors (alcohol, chat, smoking) on immunological outcomes were observed. This vaccine elicited significant immunological responses in diabetic patients, characterized by initial increases in inflammatory markers and subsequent stabilization, and with implications for the healthcare policies to design tailored approaches for diabetic groups.